Is crowd support a significant factor in home advantage on the highest level of competition in football? - Jaguszewski, Maciej (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Home advantage is an important factor in determining the result of a football game. Crowd support is considered to be a major factor influencing home advantage, but it has not been verified individually on the professional level. Due to the COVID-19 pandemic, football matches started to be held without the participation of an audience, which gave an opportunity to examine crowd effects. In this article the impact of crowd effects was examined on the highest level of competition, in four best European leagues. Aim of Study. The aim of the study was to check if crowd support is an important factor in home advantage in four best European football leagues and to examine tendencies in home advantage in those leagues from 2015 to 2020. Material and Methods. Football match results from 2015 to 2020 in the Spanish, English, German and Italian leagues were collected and used in the analysis. Two coefficients: Home Advantage Rate and Difference between percentage of home team wins and losses were used. Statistical calculations were carried out using the STATISTICA software package. Results. It was noticed that in Spain and in Germany home teams performed worse in matches without an audience than in those with crowd support. However, in England and in Italy the results of home teams with and without crowd presence were similar. Moreover, home advantage has been decreasing in recent years in the best European leagues. Conclusions. There is a statistically significant impact of crowd support on home advantage on the highest level of competition in football.
Keywords: football; home advantage; crowd effects